2022
DOI: 10.3389/fnut.2022.818632
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Associated Factors of Weight Gain During the Covid-19 Pandemic

Abstract: Introduction and AimsThe behavioral changes that arose from quarantine due to the COVID-19 pandemic may have impacted the weight of people. This study aims to investigate the incidence and predictors of weight gain during the quarantine period.MethodsAn online survey was performed five months after the social distance measures implementation. Participants recorded their current and usual weight before lockdown. A multivariate logistic regression model was performed.ResultsData on 1334 participants were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
3
5
0
Order By: Relevance
“…In the same manner, El Zoghbi et al (22) reported that the number of overweight and obese students increased by 5.2% in a study conducted on 174 Lebanese students before and at the end of the COVID-19 lockdown. Consistent findings were also reported in Srilanka (23), Brazil (24), Spain (25), and Bangladesh (26) where participants gained weight during the pandemic period. These findings are distressing because increasing adiposity had been associated with higher odds for COVID-19-related mortality in previous trials.…”
Section: Discussionsupporting
confidence: 82%
“…In the same manner, El Zoghbi et al (22) reported that the number of overweight and obese students increased by 5.2% in a study conducted on 174 Lebanese students before and at the end of the COVID-19 lockdown. Consistent findings were also reported in Srilanka (23), Brazil (24), Spain (25), and Bangladesh (26) where participants gained weight during the pandemic period. These findings are distressing because increasing adiposity had been associated with higher odds for COVID-19-related mortality in previous trials.…”
Section: Discussionsupporting
confidence: 82%
“…Evidence has demonstrated that the period of COVID-19-associated social isolation was responsible for body mass gain in the general population. Daniel et al 33 evaluated the eating behavior of 1334 participants during five months of the COVID-19 pandemic. In this study, the authors found a 58.8% increase in body mass (approximately 3 kg), which was mainly associated with increased consumption of snacking, fast food, canned products, and sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The state of depression or the worsening of this condition are precursors to weight gain ( 48 ). Daniel and collaborators ( 49 ) revealed in their study that an increase in uncontrolled eating behavior was a predictor of weight gain during the pandemic. Thus, these behaviors are relevant influences on food choices and, consequently, on BMI ( 50 ).…”
Section: Discussionmentioning
confidence: 99%